A Comparative Study of PTS and Manual Transportation for Platelet Count and Aggregation Test - Sri Suryo Adiyanti; Bernadette Elvina Setiadi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
The transportation effect of the Pneumatic Tube System (PTS) on platelet activity remains controversial. This study aimed to analyze the effect of PTS in the platelet aggregation test in Dr. Cipto Mangunkusumo Hospital, Jakarta. This cross-sectional study was carried out in the Clinical Pathology Laboratory of Dr. Cipto Mangunkusumo Hospital (RSUPNCM) from March to April 2021. There were 50 subjects involved in this study, each of whom 6 sodium citrate blood tubes were extracted. Three tubes were sent through PTS while the rest were transported manually. All tubes were then tested for platelet count and platelet aggregation using ADP agonists of 1 uM, 5 uM, and 10 uM. There was a lower platelet count (p=0.046) and platelet aggregation in ADP 1 uM (p=0.037), ADP 5 uM (p <0.001), and ADP 10 uM (p <0.001) at PTS-transported samples. Eleven samples were interpreted distinctively as low platelet aggregation in PTS transportation became normal in manual delivery. Cohen’s Kappa value was 0.51 (p <0.001). A decreasing platelet count and platelet aggregation in PTS samples indicated that acceleration and deceleration during transportation could lead to platelet activation, thus resulting in a lower result after being added to an agonist. Cohen's Kappa test showed that manual transportation could not be replaced with PTS for the platelet aggregation test. Platelet count and platelet aggregation were found to be lower in PTS-transported samples. It was suggested to centralize specimen taking for platelet aggregation tests, thus manual transportation can be conducted more efficiently.